Casting Light on Central Bank Digital Currencies - Mancini Griffoli, Tommaso; Agur, Itai.; Ari, Anil.; Martinez Peria, Maria (Washington, D.C. : International Monetary Fund, 2018)
Digitalization is reshaping economic activity, shrinking the role of cash, and spurring new digital forms of money. Central banks have been pondering wheter and how to adapt. One possibility is central bank digital currency (CBDC)-- a widely accessible digital form of fiat money that could be legal tender. This discussion note proposes a conceptual framework to assess the case for CBDC adoption from the perspective of users and central banks. It discusses possible CBDC designs, and explores potential benefits and costs, with a focus on the impact on monetary policy, financial stability, and integrity. This note also surveys research and pilot studies on CBDC by central banks around the world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet